P5_6 White Elephants - Irwin, Benedict; Hicks, Peter; Lerman, Hannah (Physics Special Topics, 2013)
The government recently gave the go ahead for the construction of Hinkley C, a 3260MW nuclear power plant. The project will cost Â£16bn. We investigate the power output achievable if the money was instead spent on constructing onshore wind farms. We find the total energy produced from the nuclear plant is 1.63 times that of the wind farms over an 80 year window.